RFID cat door / Muhammad Rifqi Ghazali & Muhammad Firdaus Ab Halim - Ghazali, Muhammad Rifqi; Ab Halim, Muhammad Firdaus (2015)
Some people have cats, while some people don't. The problem is that, the owners have to open the door for cats every time they want to come in. Not only just that, some stray cats will eventually follow the cats and making a mess in the house. Plus, it is for the safety of the cats too. RFID cat door lock was invented to overcome the problem. This project can detect the owner's cat using radio frequency and proximity sensor to lock and unlock the cat door. This project has capability to keep away stray cat from entering the house protects the owner's cat. This project uses sensors, microcontroller and solenoid. The sensors used for this project are RFID sensor, proximity sensor and Hall Effect sensor. The microcontroller used was arduino uno R3 and solenoids were used for the linear solenoid. The circuit constructed and the simulation was tested. The simulation result was same as the expected result.